The influence of movement’s observation on recuperation after physical fatigue - Aleksandrov, A.; Deinekina, T.; Mathiassen, Svend; Lyskov, E. (2014)
© 2014, Maik Nauka-Interperiodica Publishing. All rights reserved. The study aim was to investigate effects of mental activity, accompanied by mu-rhythm depression, on recuperation after physical fatigue. In a study participants performed 11 one minute bouts of static hand grip intermitted by 2 minutes rest pauses. During pauses participants watched video with either dynamic hand grips (biological movements) or deformation of geometric figure (control). Obtained data showed there was a significant depression of mu-rhythm during biological movement’s observation. There was significant fatigue of subjects in an exercise with physical activity, but there was no reliable influence of performed mental activity on recovery after fatigue.